Evaluation of Metastasis-Associated Lung Adenocarcinoma Transcript 1 (MALAT 1) and H19 in Determining the Diagnosis and Severity of the Disease in Patients with Acute Pancreatitis - Karahan, Hafize Tugba; Tanoglu, Alpaslan; Tanoglu, Esra Guzel; Gokce, Muhammed Said; Karahan, Erdem (Turkish Journal of Gastroenterology, 2025)
Background/Aims: This current research targeted to assess whether long non-coding RNAs MALAT1 and H19, which are accepted to act a pivotal role in the progression of acute pancreatitis (AP), can be used as candidate biomarkers in addressing the diagnosis and severity of AP. Materials and Methods: Healthy volunteers who applied to the Internal Medicine outpatient clinic between October 2022 and June 2023 and patients who were hospitalized and treated for AP in the same period were enrolled in the research. The sociodemographic charac teristics, biochemical values, and expression levels of MALAT1 and H19 of the study participants were compared. Results: There was no difference in terms of H19 level among the patient and healthy individuals (P = .619). However, a marked upregula tion of MALAT1 expression was observed in cases of AP (P = .018). In addition, a range of biochemical markers showed notable disparities between the patient cohort and healthy individuals. Conclusion: According to the results of this current study, because the MALAT1 levels were significantly increased in AP cases, it could be postulated that MALAT1 can be used as a candidate biomarker in AP cases in order to diagnose the illness. However, MALAT1 and H19 did not correlate with the severity of the disease. Cite this article as: Karahan HT, Tanoglu A, Tanoglu EG, Gokce MS, Karahan E. Evaluation of metastasis-associated lung adenocarcinoma transcript 1 (MALAT 1) and H19 in determining the diagnosis and severity of the disease in patients with acute pancreatitis. Turk J Gastroenterol. Published online November 6, 2025. doi:10.5152/tjg.2025.24701.